Comparison of selected methods for measuring the luminous flux of solid-state light sources - Górecki, Krzysztof; Kalinowska, Aleksandra; Ptak, Przemysław (Opto-Electronics Review, 2024)
The paper presents a simple method of measuring the luminous flux value dedicated to LED light sources. This method uses information about a spatial radiation pattern of the lighting source under test and the results of illuminance measurements at the axis of this source. The method is described and the results of the measurements obtained using this method and the classical method are compared and discussed. Tests have been carried out for LED modules of different geometries. The measurement error of the considered method is analysed.